Graduate study and its impact on the professional life - Rolim, Karla Maria Carneiro; Bezerra, Maria Gorette Andrade; Moreira, Vládia Teles; Rodrigues, Maria do Socorro Pereira (Rev Rene, 2003)
A study was made during the year of 2002, to describe on a qualitative basis, the impact of master or doctoral degree in the life of nurses that took a graduate course at the Federal University of Ceará. Thirteen persons with a master degree and three with a doctoral degree participated in this study. The data was collected through questionnaires and analyzed following Bardin’s method (1976). Three categories were analyzed: the impact on their professional, social, and family life. The conclusion is that a graduate course is very important, because it leads the professional to a new and more scientific view.